2021
DOI: 10.1097/iop.0000000000001931
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Antioxidant Effects of Selenium on Orbital Fibroblasts of Patients With Graves Ophthalmopathy

Abstract: Purpose: In the present study, the authors investigated the effects of selenium on inflammation, hyaluronan production, and oxidative stress in primary cultured orbital fibroblasts of patients with Graves ophthalmopathy (GO). Methods: Orbital adipose/connective tissue specimens were obtained during the course of orbital surgery for patients with GO (n = 7) and other noninflammatory problems (n = 5). After incubation with various concentrations of sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…One randomized clinical trial of selenium supplementation in patients with mild Graves’ orbitopathy was performed, and the quality of life and eye disease parameters improved significantly after 6 months of treatment ( 120 , 121 ). Recently, it was reported that selenium suppressed hyaluronan production, inflammatory cytokines, and intracellular ROS generation in cultured orbital fibroblasts of patients with Graves’ orbitopathy (GO), suggesting a basis for the use of selenium in the treatment of GO ( 122 ).…”
Section: Selenium Supplementationmentioning
confidence: 99%
“…One randomized clinical trial of selenium supplementation in patients with mild Graves’ orbitopathy was performed, and the quality of life and eye disease parameters improved significantly after 6 months of treatment ( 120 , 121 ). Recently, it was reported that selenium suppressed hyaluronan production, inflammatory cytokines, and intracellular ROS generation in cultured orbital fibroblasts of patients with Graves’ orbitopathy (GO), suggesting a basis for the use of selenium in the treatment of GO ( 122 ).…”
Section: Selenium Supplementationmentioning
confidence: 99%
“…[ 104 ] In several in vitro studies, selenium reduces H 2 O 2 -induced oxidative stress, proliferation, hyaluronan synthesis,[ 105 ] and proinflammatory cytokine production in OFs. [ 106 107 ] Controversy exists regarding the association of selenium levels with the severity or activity of TED. [ 108 109 ] The value of supplemental selenium on antithyroid drug medication in GD is still debatable in some randomized, controlled trials, especially in a selenium-sufficient cohort of GD.…”
Section: Seleniummentioning
confidence: 99%
“…Finally, 20 papers met the inclusion criteria and were considered in this review [ Figure 1 ]. There were four human studies 20 21 22 23 and sixteen in vitro studies 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 from 1993 to 2021 [ Table 2 ]. Fifteen studies were from Taiwan (2), Canada (1), Greece (1), Brazil (2), Poland (1), the USA (1), Japan (1), Italy (5), South Korea (3), Germany (1), China (1), and one was supervised by the international multicentral European Group on Graves' Orbitopathy (EUGOGO) association.…”
Section: R Esultsmentioning
confidence: 99%